Fluvial Sedimentology and Paleoecology of Holocene Alluvial Deposits, Red River, Manitoba - Nielsen, Erik; McKillop, W.; Conley, Glen (Géographie physique et Quaternaire, 1993)
ABSTRACTStratigraphie and paleoecological analyses at five sections, together with age determinations based on 19 previously published and 21 new radiocarbon dates, provide a detailed late Holocene history of the Red River, Manitoba. Ecological information, such as age frequency analysis, relative abundance, diversity and association of species was drawn from 19 mollusc species. These data indicate that the Red and Assiniboine rivers cut the valleys they occupy today within a thousand years of the regression of Lake Agassiz. In the south, up to 14 m of alluvium has accumulated during the last 7000 years. A decrease in the sedimentation rate at 1400 BP is coincident with the shift in the position of the Assiniboine from the valley of the La Salle River to its present position. Overbank sedimentation did not start in the northern part of the area until ca. 5200 BP. Initial rapid sedimentation rates in this area are attributed to increased precipitation and a brief eastward excursion of the Assiniboine River into the Red. In spite of increased precipitation, flood frequencies remained low in the north until 1400 BP. Increased overbank sedimentation after 1400 BP is attributed to the northward shift in the position ot the Assiniboine.